2021
DOI: 10.1055/a-1398-2197
|View full text |Cite
|
Sign up to set email alerts
|

Zusammenhang zwischen dem Lesen nicht-medizinischer Bücher mit Burnout und beruflicher Zufriedenheit bei Urologen mit Migrationshintergrund – Ergebnisse einer Fragebogenstudie an deutschen Kliniken

Abstract: Zusammenfassung Hintergrund Es liegen aktuell keine Studienergebnisse zur privaten und beruflichen Zufriedenheit sowie zum Burnout-Risiko von Urologe*innen mit Migrationshintergrund an deutschen Kliniken vor. Der Einfluss des Lesens nicht-medizinischer Bücher auf geringere Burnout-Raten bei Ärzte*innen verschiedener Fachrichtungen wurde beschrieben. Material und Methoden Ein Survey-Monkey mit 101 Items zu charakterisierenden Kriterien des Studienteilnehmers, Fragen zur privaten un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Another recently published study within the EUTAKD study underlines the necessity to optimize the professional and private integration process for physicians in this important professional group [6]. In this analysis, evidence for a high risk of burnout, consisting of emotional exhaustion and/or depersonalization, was found in 41.2% of the study participants [6].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Another recently published study within the EUTAKD study underlines the necessity to optimize the professional and private integration process for physicians in this important professional group [6]. In this analysis, evidence for a high risk of burnout, consisting of emotional exhaustion and/or depersonalization, was found in 41.2% of the study participants [6].…”
Section: Discussionmentioning
confidence: 88%
“…The survey was carried out in the form of SurveyMonkey ® (SurveyMonkey Inc., San Mateo, CA, USA) which was open for study participation from August 1 to October 31, 2020. To publicize the EUTAKD study, access to SurveyMonkey ® was advertised by means of a QR code via corresponding articles in the magazines Uro-Forum and Uro-News and in an information campaign via the "Gesellschaft der urologischen Assistenzärzte" (GESRU) [6][7][8][9]. In addition, the chairs of all the regional specialist urological societies were written to twice and asked to help by passing on the study invitation to the various clinics under their purview.…”
Section: Study Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, there are multiple potential stressors and future research needs to explore which mechanisms are important for which group of physicians, in terms of cultural background, age, gender, etc., at which state of the acculturation process. In addition, some physician behaviors could represent helpful resources as a recent German study showed that urologists with an MB exhibited a lower risk of burnout when they read more nonmedical books [39].…”
Section: Discussionmentioning
confidence: 99%